Decidual Macrophage Functional Polarization during Abnormal Pregnancy due to Toxoplasma gondii: Role for LILRB4 - Li, Zhidan; Zhao, Mingdong; Li, Teng; Zheng, Jing; Liu, Xianbing; Jiang, Yuzhu; Zhang, Haixia; Hu, Xuemei (Frontiers in Immunology, 2017)
During gestation, Toxoplasma gondii infection produces a series of complications including stillbirths, abortions, and congenital malformations. The inhibitory receptor, LILRB4, which is mainly expressed by professional antigen-presenting cells (especially macrophages and dendritic cells) may plays an important immune-regulatory role at the maternal–fetal interface. To assess the role of LILRB4 during T. gondii infection, LILRB4−/− and T. gondii infected pregnant mouse models were established. Further, human primary-decidual macrophages were treated with anti-LILRB4 neutralizing antibody and then infected with T. gondii. These in vivo and in vitro models were used to explore the role of LILRB4 in T. gondii-mediated abnormal pregnancy outcomes. The results showed that abnormal pregnancy outcomes were more prevalent in LILRB4−/− infected pregnant mice than in wild-type infected pregnant mice. In subsequent experiments, expression levels of LILRB4, M1, and M2 membrane functional molecules, arginine metabolic enzymes, and related cytokines were assessed in uninfected, infected, LILRB4 neutralized infected and LILRB4−/− infected models. The results demonstrated T. gondii infection to downregulate LILRB4 on decidual macrophages, which strengthened M1 activation functions and weakened M2 tolerance functions by changing M1 and M2 membrane molecule expression, synthesis of arginine metabolic enzymes, and cytokine secretion profiles. These changes contributed to abnormal pregnancy outcomes. The results of this study provide not only a deeper understanding of the immune mechanisms operational during abnormal pregnancy, induced by T. gondii infection, but also identify potential avenues for therapeutic and preventive treatment of congenital toxoplasmosis.